Say it like Obama the power of speaking with purpose and vision - Leanne, Shelly (New York McGraw-Hill, 2009)
Obama's outstanding communication skills gave rise to an unprecedented political movement and fueled his success. This book is about the art of persuasion, the power of presentation, and the most effective techniques of communication.
The speech that started it all -- Earning trust and confidence -- Breaking down barriers -- Winning hearts and minds -- Conveying vision -- Driving points home -- Persuading -- Facing and overcoming controversy -- Motivating others to action and leaving strong last impressions -- The speech that made history-- again.
Keywords: Obama, Barack -- Oratory; Public speaking; Persuasion (Rhetoric); Success in business